Peculiarities of Evaluating the Activity of Scientific Organizations in Some Countries of the Former USSR - Zhukovych І. A. (Statistics of Ukraine, 2022)
Methodological approaches and peculiarities of evaluating the activity of research institutions in the countries of the former USSR are considered. Thus, in the Republic of Kazakhstan, according to the "Methodology for evaluating the activity of entities of scientific and (or) scientific and technical activity", each indicator is assigned to a certain block provided in the "Rating list of entity". The significance of indicators in blocks is regulated by feasible parameters. The quality of scientific and scientific and technical activities is determined by summing up the integral assessments for all blocks. According to the total number of points received, the commission makes a decision on the recommendation of the entity of scientific and technical activity for accreditation. In the Republic of Armenia, a rating model for evaluating the results of their activities is used to distribute the basic funding of scientific institutions. The evaluation takes place according to seven criteria, represented by indicators, which are used to calculate the coefficient of evaluation of the effectiveness of the scientific activity of the institution. At the same time, pre-formed groups of institutions engaged in scientific activities in similar fields of scientific research are subject to evaluation. In the Republic of Uzbekistan, with the goals of creating a competitive environment in the field of scientific research and development, stimulating an increase in the level and quality of scientific activity, ensuring effective mechanisms for managing the scientific sphere, rational use of scientific potential and financial resources, the "Methodology for determining the rating of scientific institutions" was approved. The framework of the rating is based on the principles of impartiality, transparency and fairness, as well as criteria determined by indicators. Indicators are calculated according to formulas, based on the results of which points are determined. According to the points, a ranking of institutions is formed and they are divided into groups. The conclusion is as follows that in the considered countries of the former USSR, preference is given to a quantitative approach aimed at obtaining a final assessment in the form of a single numerical indicator. Such an assessment does not include the quality of research and the specificity of activities in various fields of science, does not reflect the importance of the results, and therefore does not characterize the effectiveness of a specific scientific institution. The mentioned approach raises questions about its objectivity, as it does not allow to avoid manipulations with the assignment of certain points, which occurs artificially. The difference in the methods used to evaluate the effectiveness of scientific institutions in Ukraine is indicated.